2010
DOI: 10.1007/s10815-010-9416-5
|View full text |Cite
|
Sign up to set email alerts
|

Extended in vitro maturation of immature oocytes from stimulated cycles: an analysis of fertilization potential, embryo development, and reproductive outcomes

Abstract: Efficacy of 24 h IVM for cumulus-stripped GV and MI oocytes for either clinical use or study of normal meiotic maturation is questionable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 41 publications
3
33
1
Order By: Relevance
“…Despite the fact that these denuded oocytes are not fully developmentally competent, they constitute a very interesting and useful source of human material, limiting the randomization of patients' oocytes for studies. As suggested by several authors, immature oocytes from stimulated cycles can be matured in vitro creating a potential source of human oocytes for experimental research despite their inferior quality [34,35]. Additional studies are required, however, to confirm our results, to improve the oocyte developmental competence after IVM and vitrification procedures and to explore new methods in human oocyte cryopreservation techniques.…”
Section: Discussionsupporting
confidence: 57%
“…Despite the fact that these denuded oocytes are not fully developmentally competent, they constitute a very interesting and useful source of human material, limiting the randomization of patients' oocytes for studies. As suggested by several authors, immature oocytes from stimulated cycles can be matured in vitro creating a potential source of human oocytes for experimental research despite their inferior quality [34,35]. Additional studies are required, however, to confirm our results, to improve the oocyte developmental competence after IVM and vitrification procedures and to explore new methods in human oocyte cryopreservation techniques.…”
Section: Discussionsupporting
confidence: 57%
“…In vitro maturation followed by fertilization opens a new avenue to make full use of the immature oocytes derived from controlled ovarian stimulation cycles. Several studies [1,6,9,12,17,27,32,34,35,41] have reported how to use the immature oocytes; however, the detailed influence of CCs on the developmental potential of human immature oocytes has not been extensively examined. In this study, our results indicated that, although there was no significant difference in the proportion of oocytes that reached metaphase II with the presence or absence of cumulus cells, it was noteworthy that an improvement in developmental potential was observed in the immature oocytes with CCs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that these in vitro matured oocytes lead to lower fertilization rates [1,9,34], abnormal embryonic development [1,4,34], and lower implantation rates [9] compared to oocytes that maturate in vivo. In these studies, the removal of cumulus cells from oocytes was performed after their retrieval before in vitro culture [1,6,9,27,32,34,35,41]. Some authors [16,17] also reported the developmental potential of immature oocytes that were not denuded of their cumulus cells (CCs) on the day of retrieval.…”
Section: Introductionmentioning
confidence: 99%
“…Even without freezing, in vitro matured oocytes are still not up to par with their in vivo counterparts [47,48], and the currently low efficiency of GV freezing may thus reflect additive negative effects of IVM, as well as cryopreservation. In an effort to compensate or perhaps even remedy some of the stresses associated with cryopreservation, IVM culture media may need to be tailored for use with cooled/ warmed GV oocytes.…”
Section: Discussionmentioning
confidence: 99%